2004
DOI: 10.1152/ajpheart.00110.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum calcium defect in Ras-induced hypertrophic cardiomyopathy heart

Abstract: The small G protein Ras-mediated signaling pathway has been implicated in the development of hypertrophy and diastolic dysfunction in the heart. Earlier cellular studies have suggested that the Ras pathway is responsible for reduced L-type calcium channel current and sarcoplasmic reticulum (SR) calcium uptake associated with sarcomere disorganization in neonatal cardiomyocytes. In the present study, we investigated the in vivo effects of Ras activation on cellular calcium handling and sarcomere organization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 36 publications
7
66
0
Order By: Relevance
“…There has been significant interest in understanding the molecular and cellular adaptations leading to hypertrophy caused by HCM, hypertension, and valvular disease. Several studies have shown that although the inward calcium current (I Ca ) through the L-type calcium channel is not altered in hypertrophic or failing rat and murine cardiomyocytes, there is a decrease in the intracellular calcium transient, [Ca] I [33,34]. In post-myocardial infarction cardiomyocytes, this normal I Ca and decreased intracellular calcium transient, [Ca] i , was shown to be independent of SR calcium concentration [35].…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant interest in understanding the molecular and cellular adaptations leading to hypertrophy caused by HCM, hypertension, and valvular disease. Several studies have shown that although the inward calcium current (I Ca ) through the L-type calcium channel is not altered in hypertrophic or failing rat and murine cardiomyocytes, there is a decrease in the intracellular calcium transient, [Ca] I [33,34]. In post-myocardial infarction cardiomyocytes, this normal I Ca and decreased intracellular calcium transient, [Ca] i , was shown to be independent of SR calcium concentration [35].…”
Section: Discussionmentioning
confidence: 99%
“…The notion that HCM in Costello syndrome is driven by Ras/MAPK activation is supported by the recent description of a transgenic mouse model where targeted expression of an HRas-G12V mutant has Costello syndrome features and develops significant cardiac hypertrophy [Zheng et al, 2004]. A zebrafish model of Costello syndrome expressing oncogenic H-RASV12 also had thicker heart walls [Santoriello et al, 2009], but the observed defects in early heart morphogenesis cannot be directly compared to humans with Costello syndrome (most of whom have the p.G12S mutation).…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Recent work has suggested that the selective induction of Gαi in the RAS transgenic heart contributes to impaired sarcoplasmic reticulum calcium cycling (97), and a number of other studies have led to descriptions of RAS-induced alterations in calcium transients (98)(99)(100). Interestingly, abnormalities in delicate calcium homeostasis can trigger cardiac hypertrophy through mechanisms that have not been fully elucidated (101).…”
Section: Cooperative Effects On the Ras Pathway: Cross-links In Hypermentioning
confidence: 99%